Respiration of Microbiota-Derived 1,2-propanediol Drives Salmonella Expansion during Colitis. - Franziska Faber; Parameth Thiennimitr; Luisella Spiga; Mariana X Byndloss; Yael Litvak; Sara Lawhon; Helene L Andrews-Polymenis; Sebastian E Winter; Andreas J Bäumler (PLoS Pathogens, 2017)
Intestinal inflammation caused by Salmonella enterica serovar Typhimurium increases the availability of electron acceptors that fuel a respiratory growth of the pathogen in the intestinal lumen. Here we show that one of the carbon sources driving this respiratory expansion in the mouse model is 1,2-propanediol, a microbial fermentation product. 1,2-propanediol utilization required intestinal inflammation induced by virulence factors of the pathogen. S. Typhimurium used both aerobic and anaerobic respiration to consume 1,2-propanediol and expand in the murine large intestine. 1,2-propanediol-utilization did not confer a benefit in germ-free mice, but the pdu genes conferred a fitness advantage upon S. Typhimurium in mice mono-associated with Bacteroides fragilis or Bacteroides thetaiotaomicron. Collectively, our data suggest that intestinal inflammation enables S. Typhimurium to sidestep nutritional competition by respiring a microbiota-derived fermentation product.